Reviewing the evidence on effectiveness and cost-effectiveness of HIV prevention strategies in Thailand - Teerawattananon Yot; Pattanaphesaj Juntana (BMC, 2010)
Abstract Background Following universal access to antiretroviral therapy in Thailand, evidence from National AIDS Spending Assessment indicates a decreasing proportion of expenditure on prevention interventions. To prompt policymakers to revitalize HIV prevention, this study identifies a comprehensive list of HIV/AIDs preventive interventions that are likely to be effective and cost-effective in Thailand. Methods A systematic review of the national and international literature on HIV prevention strategies from 1997 to 2008 was undertaken. The outcomes used to consider the effectiveness of HIV prevention interventions were changes in HIV risk behaviour and HIV incidence. Economic evaluations that presented their results in terms of cost per HIV infection averted or cost per quality-adjusted life year (QALY) gained were also included. All studies were assessed against quality criteria. Results The findings demonstrated that school based-sex education plus life-skill programs, voluntary and routine HIV counselling and testing, male condoms, street outreach programs, needle and syringe programs, programs for the prevention of mother-to-child HIV transmission, male circumcision, screening blood products and donated organs for HIV, and increased alcohol tax were all effective in reducing HIV infection among target populations in a cost-effective manner. Conclusion We found very limited local evidence regarding the effectiveness of HIV interventions amongst specific high risk populations. This underlines the urgent need to prioritise health research resources to assess the effectiveness and cost-effectiveness of HIV interventions aimed at reducing HIV infection among high risk groups in Thailand.